2015
DOI: 10.1007/s11356-015-5817-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of CO2 emissions on economic growth: evidence from selected higher CO2 emissions economies

Abstract: The main purpose of this work is to analyze the impact of environmental degradation proxied by CO2 emissions per capita along with some other explanatory variables namely energy use, trade, and human capital on economic growth in selected higher CO2 emissions economies namely China, the USA, India, and Japan. For empirical analysis, annual data over the period spanning between 1971 and 2013 are used. After using relevant and suitable tests for checking data properties, the panel fully modified ordinary least s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(75 citation statements)
references
References 38 publications
5
54
0
Order By: Relevance
“…Leitao [26] found a significant positive relationship between CO 2 emissions and economic growth in Portugal. Azam et al [27] proved the same case for China, Japan, and the USA, while it is found significantly negative in case of India.…”
Section: Literature Reviewmentioning
confidence: 71%
“…Leitao [26] found a significant positive relationship between CO 2 emissions and economic growth in Portugal. Azam et al [27] proved the same case for China, Japan, and the USA, while it is found significantly negative in case of India.…”
Section: Literature Reviewmentioning
confidence: 71%
“…A sequence of time series techniques has been employed to investigate the relationship between urbanization, energy use, and carbon emissions in the BRICS countries. This study follows the methodology applied by recent study of Azam et al in case of some selected countries. First, study conducts five panel unit root tests to examine the stationary properties of the underlying variables.…”
Section: Empirical Methodologymentioning
confidence: 99%
“…The results indicated that fossil energy consumption have negative impacts on CO2 emission levels in Texas while energy consumption having positively influence on CO2 emissions in Florida but this impact is lower as compared to other states of US. Azam et al (2016) inspected the influences of CO2 emissions, energy use, trade, and human capital on economy growth from 1971 and 2013 for China, the USA, India, and Japan by utilizing panel fully modified ordinary least squares (FMOLS) for checking the association among the study variables. The examined results pointed out that CO2 emissions and energy consumption negatively and significantly influences the economic growth while trade and human capital positively and significantly influences the economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%